Análise e dimensionamento de vigas mistas de aço e concreto com protensão externa - Ribeiro, Karla Demoner (2018)
Steel and concrete composite beam is an efficient structural system to support gravitational loads of floors and buildings because it is ease to construction and it reduces the weight of the steel beam. Searching for new materials and constructive technologies, it was observed that the external prestressed is one of the techniques adopted to improve the structural behavior of a material. In Brazil, prestressed steel and concrete structures is still not widely used, because there is very little disclosure about it and there‟s a lack of clear norms and formulations about it. There are analytical studies on prestressed composite beams, but there is a lack of works in the literature about design methodologies. This work aims to discuss methodologies which deals with the analysis and the designing of steel and concrete composite beams simply supported with "I" steel sections double symmetrical and monosymmetric using the pre tensioning technique. A computational program was developed to perform the analysis and the desing of these beams, based on the calculation methodology of ABNT NBR 8800: 2008 and in the stresses analysis, which is tested comparing with a manually solved example. Using the computer program, a parametric study was carried out to analyze the influence of the length of the span, the degree of monosymmetry of the cross section of the steel profile and the eccentricity of the prestressing force in the resistant capacity of the beams. The results of the research indicate that although the prestressing has generated a considerable improvement in the behavior of the composite beams to the flexion, reducing the acting bending moment and increasing the resistant bending moment, there was little advantage in relation the to the optimization of the steel profile because the force of pretension introduces compression stresses. The effects of the prestressing were much more beneficial for the beams of double symmetrical profile than for the ones of monosymmetrical profile. In this research it was not possible to conclude which eccentricity provides the greatest flexural resistance since there was no considerable variation in resistance when there is variation in this parameter.